Strategi Guru dalam Menanamkan Nilai-Nilai Kewarganegaraan pada Siswa dalam Membangun Karakter Demokratis dan Tanggung Jawab Sosial - Jesmi Jesmi; Syamzaimar Syamzaimar (International Forum of Researchers and Lecturers, 2026)
This study examines teachers’ strategies in instilling citizenship values among students to develop democratic character and social responsibility. The background of this study is rooted in the increasing need to strengthen students’ civic awareness and character in the face of rapid social and technological changes. The objective of this research is to identify and analyze effective strategies used by teachers in integrating citizenship values into the learning process. This study employs a library research method by analyzing various relevant academic sources, including journals, books, and scholarly articles related to citizenship education and character development. The findings indicate that effective strategies include student-centered learning approaches, the integration of character education into civic education, the use of inquiry-based learning methods, and the utilization of technology to enhance student engagement. Additionally, extracurricular activities and a democratic classroom environment play a significant role in reinforcing students’ understanding and application of citizenship values. These strategies contribute to the development of students’ critical thinking, participation skills, and social awareness. The implications of this study suggest that teachers need to continuously innovate and adapt their teaching strategies to meet the evolving needs of students and societal demands. Furthermore, educational institutions should provide adequate support and resources to optimize the implementation of citizenship education in fostering responsible and democratic citizens.